Safe Harbor Legislation for Juvenile Victims of Sex Trafficking: A Myopic View of Improvements in Practice - Kimberly Mehlman-Orozco (Social Inclusion, 2015)
Current social and political realties have focused attention on human trafficking in the United States. Although new mechanisms for criminalizing offenders and protecting victims are increasingly funded and implemented across the country, empirical exploration into the efficacy of these interventions is lacking. This article uses yearly count data on juvenile prostitution arrests aggregated at the state level to explore the criminalization of commercial sexually exploited children post safe harbor policy implementation. Preliminary data from four states suggests that the passage of safe harbor laws may not reduce the number of juveniles arrested for prostitution crimes. Implications for future research are discussed.